The Effect of Educational intervention base on Health Belief Model on performing Pap smears in women of Fasa city - Zahra Khiyali; Razieh Asadi; Afsaneh Ghasemi; Ali Khani Jeihooni (Iranian Association of Health Education and Health Promotion, 2017)
Background and Objective: Pap smear test is a cervical cancer screening tool that plays an important role in the early detection, prevention and delay of progression of the cervical disorder. Therefore, this study aimed to determine the effect of educational intervention on performing pap smear in women of Fasa city.   Materials and Methods: This quasi-experimental study were performed on 160 women referred to Fasa Health Centers (80 individuals in experimental and 80 in the control group) in 2015. The data collection tools were demographic questionnaires, Knowledge and performance questionnaires and HBM constructs in the field of pap smear which was completed before and two months after the intervention. The educational program for the test group was conducted during 5 sessions in a discussion group with the presentation of educational pamphlets. The findings were analyzed by SPSS 22 software at the significance level of P <0.05. Results: The mean scores of awareness and HBM model constructs (susceptibility, severity, benefit and perceived barriers) were significantly increased in the experimental group compared to the control group after the intervention (P <0/05). Also, 51.25% of women performed pap Smear test that was statistically significant (P <0.001). Conclusions: Improving the performance of the Pap smear tests in women support the implementing a training program and taking advantage of the health belief model for cervical cancer screening.